Understanding and quantifying the environmental impact of sterile medical devices: a carbon footprint study of single-use electrosurgical scalpels and their reusable alternatives - David Feldman; Chloé Couret; Johann Clouet; Annabel Goubil; Kimberley Lefèvre; Mireille Ferlita; Elise Rochais (BMJ Surgery, Interventions, & Health Technologies)
Background In France, 25% of healthcare emissions are attributed to the supply of medical devices, underscoring the necessity for the development of more sustainable procurement policies. However, comparing the carbon footprint of different devices, especially single-use devices versus reusable ones, presents challenges.Objective To assess the carbon footprint of single-use and reusable electrosurgical scalpels over 1 year of use in our hospital setting.Design A cradle-to-grave analysis was conducted from May 1, 2022, to April 30, 2023.Setting Nantes University Hospital, France.Main outcome measures The study quantifies carbon emissions across all life cycle stages: raw material extraction, manufacturing, transportation, use, maintenance, and disposal. For reusable devices, sterilization emissions were allocated based on the total annual workload of the Central Sterile Services Department. Carbon footprint values were derived from direct measurements, manufacturer and supplier data, and literature, with conversions using a public and national database (Base Empreinte, ADEME).Results The carbon footprint of single-use devices was estimated at 4291 kg of carbon dioxide equivalent (CO2e), with 94% attributed to the production of the device itself. The carbon footprint related to the reusable device was estimated at 494 kg CO2e, with 86% stemming from handling at our sterilization unit.Conclusions These findings are contingent on our hospital’s practices and may vary based on several factors. Beyond estimating these carbon footprints, it provides a practical, decision-oriented analysis accessible for hospital leadership and healthcare professionals, supporting institutional change.